Language techniques of artistic ideologisation in O. Gonchar’s prosaic works as manifestation of the influence of ideology on formation of the author’s idiostyle - Кохан, Юрій Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article introduces the analysis of the words and word expressions marked by the influence of the soviet ideology, that are used by Oles Gonchar for creation of images of “ideologically correct“ heroes in his works. It is noted that the ideological system is one of the factors of the author’s individual style formation and it had a great impact on selection and use of the language material by the author.Among the aspects that were analysed we should mention associative connection and compatibility of ideologically marked lexis and phraseology. Character-forming functions of lexical and phraseological units as well as axiologisation of stylistically neutral words and word combinations were found out.The lexical and phaseological units that convey the attitude of the heroes in O. Gonchar’s prosaic works to labour as to the biggest value and the sense of life have become an object of analysis. These units reproduce people’s moral principles and describe them as morally clean people who are modest in their daily life and show active citizenship. The words and expressions under analysis are not ideologemmas in terms of conventional understanding. However, they help to form images of positive characters, whose attitudes and actions correspond to moral and ideological canons of the soviet society which is conditioned by the canons of the indicated time span. That is why we consider these language units to be ideologically marked and analyse them as techniques of artistic ideologisation of heroes in O. Gonchar’s prosaic works.